Soil-Transmitted Helminthes Infection and Nutritional Status of Elementary School Children in Sorong District, West Papua, Indonesia - Salma, Zukhaila; Fitriah, Fitriah; Renaldy, Raden Bagus Yanuar; Rossyanti, Lynda; Sarjana, IWayan; Pasulu, Soraya Salle; Budiono, Budiono; Gunadi Ranu, I Gusti Made Reza; Husada, Dominicus; Basuki, Sukmawati (Indonesian Journal of Tropical and Infectious Disease, 2021)
It is known that soil-transmitted helminths (STHs) infection in children associates with growth and developed restriction in children, which is shown by nutritional status. However, the studies which are investigating this phenomenon is still limited in Indonesia. This recent study aimed to compare students who infected and non-infected with STH towards their nutritional status. An analytic cross-sectional research design was conducted in two elementary school students at Mayamuk sub-district, Sorong district, in January 2020. STHs infection was identiï¬ ed by lugol stained wet mount smear from their stool under a light microscope. Children nutritional status was determined by body mass index based on age. A total of 164 children (67.5%, 164/243) were voluntary to participate by informed consent and eligible. Twenty-seven children (16.5%, 27/164) were infected with one or more STH species of Ascaris lumbricoides, Trichuris trichiura, hookworm, and Strongyloides stercoralis. T. trichiura (81.5%, 22/27) was the most common species found, either in single or mixed infection. Children nutritional status was observed as thinness, normal, overweight, and obese, that was 6.1% (10/164), 75% (123/164), 6.7% (11/164), and 12.2 % (20/164) respectively. STHs infection occurred in children with nutritional status of thinness 3.7% (1/27), normal 74.1% (20/27), overweight 3.7% (1/27), and obese 18.5% (5/27). There was no signiï¬ cant diï¬€ erence between STHs infected children and non-infected children on their nutritional status (p=0.616, ChiSquare test). Thus, it indicated that STHs infection was not only the factor to induce the impairment of nutritional status in children at Mayamuk sub-district. It needs further investigation to clarify the factors which are leading to the thinness, overweight, and obese in Mayamuk children.